1988
DOI: 10.1103/physrevb.37.7861
|View full text |Cite
|
Sign up to set email alerts
|

Upper critical field, fluctuation conductivity, and dimensionality ofYBa2Cu3

Abstract: The upper critical Seld H, q and fiuctuation conductivity were measured for highly oriented thin nlHls of YBa2Cu307 -. The H, 2 results demonstrate the intrinsic anisotropy in this layered su-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
117
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(130 citation statements)
references
References 16 publications
12
117
0
1
Order By: Relevance
“…The obtained results are in agreement with earlier reported data [9] and our expectations since we consider temperatures very close to T c where ξ becomes large and therefore the twodimensional approximation d << ξ [11] is justified.…”
Section: Magnetoresistivity Of Ybco Thin Filmssupporting
confidence: 82%
See 2 more Smart Citations
“…The obtained results are in agreement with earlier reported data [9] and our expectations since we consider temperatures very close to T c where ξ becomes large and therefore the twodimensional approximation d << ξ [11] is justified.…”
Section: Magnetoresistivity Of Ybco Thin Filmssupporting
confidence: 82%
“…Similar B c2 (T) behavior has been demonstrated by Yeshurun [13] and Tinkham [14] with an exponent of n = 1.5 for 100 µm YBCO crystals. Also Oh et al [9] reported an upturn curvature with n = 1.3 for 1 µm thick epitaxial YBCO films using both a 0.9R n criterion and the critical fluctuation theory. The thickest studied YBCO film in this report with d = 100 nm shows a B c2 (T) dependence with the exponent n = 1.14.…”
Section: Magnetoresistivity Of Ybco Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference might be attributable to the difference in the measurement method or in the sample forms (single crystals vs. aligned powders). The good fitting results produced without the use of a C factor, 22) as well as the agreement between the obtained superconducting parameter and the literature values, indicate that the obtained parameters are reasonable.…”
Section: Methodssupporting
confidence: 77%
“…First, the zero-field, ρ ab , data was analyzed using the formula, ρ ab = 1/(ρ −1 n + σ 2D−AL ), where ρ n is the in-plane resistivity when superconductive fluctuation effects are absent and σ 2D−AL is the zero-field two-dimensional (2D) Aslamazov-Larkin (AL) form 21) In this study, ρ n is simply assumed to be ρ n = aT + b. We did not use a C factor (i.e., C = 1), 22) which is defined by the ratio of the actual ρ ab of an imperfect crystal to an ideal crystal and, thus, it phenomenologically adjusts the magnitude of the fluctuation conductivity (σ 2D−AL → σ 2D−AL /C). We optimized T c0 and ρ n to reproduce the zero-field data.…”
Section: Methodsmentioning
confidence: 99%